Combination analysis of activator protein-1 family members, Sp1 and an activator protein-2α-related factor binding to different regions of the urokinase receptor gene in resected colorectal cancers - Schewe, Denis Martin; Biller, Tobias; Maurer, Gabriele; Asangani, Irfan A.; Leupold, Jörg; Lengyel, Ernst R.; Post, Stefan; Allgayer, Heike (Clinical cancer research, 2005)
Purpose: Studies on the transactivation of genes via promoter elements have mostly been done on cell lines rather than resected tissues. This, however, is essential to address an in vivo or clinical relevance. We have previously shown tumor-specific binding of Sp1 and an activator protein (AP)-2-related factor to promoter region −152/−135 of the metastasis-related u-PAR gene in 60% of in vivo-resected cancer tissues. Cell lines have implicated an additional role, and potential synergism, of an AP-1 region (−190/−171) in u-PAR regulation. This study was done to (a) analyze AP-1 binding to this region in resected tumor and normal tissues, and define subgroups in which it is tumor-specific, and (b) to analyze transcription factor-binding patterns to both promoter motifs in resected tissues, supporting synergism, and draw first prognostic conclusions.Experimental Design: In 103 patients with colorectal cancer, electrophoretic mobility shift assay/supershift analysis for u-PAR promoter region −190/−171 was done in tumors and normal tissues. In 71 patients, region −152/−135 was also analyzed. U-PAR protein was measured by ELISA.Results: Tumor-specific AP-1 binding to region −190/−171 of the u-PAR promoter was found in 40% of patients. Subgroup analysis showed tumor-specific binding for c-Fos in 58%, for c-Jun in 50%, for JunD in 39%, and for Fra-1 in 4% of cases. AP-1 binding correlated significantly with u-PAR protein amounts in both normal and tumor tissues (P < 0.001), in contrast to a tumor-specific correlation with u-PAR of the AP-2/Sp1 region. In analyses for both promoter regions, 62% of cancers showed simultaneous binding for AP-1, AP-2, and Sp1, 11% for AP-1 and AP-2, 16% for AP-2 and Sp1, 4% for AP-2 only, 3% for AP-1 only, and 0% for Sp1 only. The binding of AP-1, AP-2, and Sp1 correlated significantly with each other (P < 0.001), the combination of AP-1 and AP-2 showing the highest correlation with u-PAR (P = 0.008). Preliminary survival analysis indicated a trend for poorer prognosis for binding of all three transcription factors.Conclusion: This is the first study differentiating transcription factor-binding to two important u-PAR promoter regions in a large series of resected tumors and normal tissues. The AP-1 site seems to be a less tumor-specific regulator than the Sp1/AP-2 motif. Nevertheless, data corroborate the hypothesis of synergism between both elements in resected tumors.